OS CUIDADOS DE ENFERMAFEM EM HEMOTERAPIA NA UNIDADE DE TERAPIA INTENSIVA NEONATAL (REMUNOM, 2025)
Introduction: Blood transfusion in the Neonatal Intensive Care Unit (NICU) is an essential procedure for the survival of neonates who are in critical conditions. Objectives: To highlight the main precautions that nursing professionals should implement during blood transfusion in neonatal intensive care units, for the safety of the blood transfusion procedure in neonatal patients, addressing the challenges faced in clinical practice and the safety protocols necessary to ensure patient safety. Methodology: This is a bibliographic study, based on the analysis of institutional protocols, published scientific articles, current standards and guidelines, through qualitative research in virtual libraries, SciELO, VHL. Final Considerations: Care in the Neonatal Intensive Care Unit (NICU) requires technical skill, scientific knowledge, supervision and humanization in the actions of the entire team from the nursing professional,aiming at the safety and well-being of the newborn, highlighting the importance of adherence to protocols and constant surveillance. The importance of adequate training and defined competencies for health professionals is emphasized, aiming at patient safety and the effectiveness of transfusion procedures.